Process for processing of granite tailings

CN118437500BActive Publication Date: 2026-10-09HUANGGANG NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410600677.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-15
Publication Date
2026-10-09
Estimated Expiration
2044-05-15

AI Technical Summary

Technical Problem

但是,受到加工深度和应用领域的限制,花岗岩尾矿的利用率仍然有限

Benefits of technology

1.对花岗岩尾矿进行筛分、磁选、浮选、酸洗的深度加工,得到高纯石英砂和低铁长石粉,应用到光伏用多晶硅用坩埚、超白玻璃、高档陶瓷原料等领域,拓宽了应用领域,提高了花岗岩尾矿的利用率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a granite tailing processing technology and relates to the field of deep processing of non-metallic mines, which comprises the following steps: taking granite tailings, adjusting pH, adding a dispersing agent, stirring and sieving to obtain a slurry, collecting the precipitate of the slurry after centrifugation to obtain pretreated ore; performing magnetic separation on the pretreated ore to remove magnetic substances to obtain demagnetized ore; taking the demagnetized ore, adjusting pH to 9-11, adding n-dodecanol, an anionic collector and a cationic collector, and performing multiple times of flotation to obtain quartz concentrate and feldspar ore; taking the quartz concentrate, performing high-temperature acid washing, stirring and leaching to obtain high-purity quartz sand. The application has the effects of obtaining 3N5-grade high-purity quartz sand and low-iron feldspar powder from granite tailings, applying the high-purity quartz sand and the low-iron feldspar powder to the fields of crucibles for polycrystalline silicon used in photovoltaics, ultra-white glass and high-grade ceramic raw materials, widening the application fields and improving the utilization rate of the granite tailings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of deep processing of non-metallic minerals, and in particular to a processing technology for granite tailings. Background Technology

[0002] Granite tailings are waste materials such as scraps, powder particles, and cooling waste liquid generated during the mining, processing, and utilization of granite. Due to limitations in mining and processing technology, the utilization rate of granite stone is only 30-40% of the mined amount, and the remaining more than 60% of tailings are stored on the surface as waste.

[0003] Currently, to reduce the accumulation of granite tailings, methods have emerged that utilize granite tailings as the main material, mixing them with other materials to produce building materials such as composite panels and microcrystalline glass. However, due to limitations in processing depth and application areas, the utilization rate of granite tailings remains limited. Summary of the Invention

[0004] In view of the shortcomings of the above-mentioned related technologies, this application provides a granite tailings processing technology, which performs deep processing of granite tailings through screening, magnetic separation, flotation and acid washing to obtain high-purity quartz sand and low-iron feldspar powder, which can be applied to fields such as polycrystalline silicon crucibles for photovoltaics, ultra-white glass, and high-grade ceramic raw materials, thus broadening the application fields and improving the utilization rate of granite tailings.

[0005] The granite tailings processing technology provided in this application adopts the following technical solution: A granite tailings processing technology includes the following steps: taking granite tailings, adjusting the pH, adding a dispersant, stirring, and then sieving to obtain a slurry; collecting the sediment from the slurry after centrifugation to obtain pretreated ore; subjecting the pretreated ore to magnetic separation to remove magnetic materials to obtain demagnetized ore; taking the demagnetized ore, adjusting the pH to 9-11, adding n-dodecyl alcohol, an anionic collector, and a cationic collector, and performing multiple flotation to obtain quartz concentrate and feldspar ore; taking the quartz concentrate, and subjecting it to high-temperature acid washing, stirring, and leaching to obtain high-purity quartz sand.

[0006] Preferably, during the process of obtaining the pretreated ore, the pH is adjusted to 9-11.

[0007] Preferably, the pH is adjusted to 10 during the process of obtaining the pretreated ore.

[0008] Preferably, sodium hexametaphosphate is used as the dispersant in the process of obtaining the pretreated ore.

[0009] Preferably, the amount of dispersant used in the process of obtaining pretreated ore is 800-1200 g / t.

[0010] Preferably, the amount of dispersant used in the process of obtaining pretreated ore is 1000 g / t.

[0011] Preferably, in the process of obtaining pretreated ore, the stirring step is as follows: stirring at a stirring speed of 1200-1800 rpm for 10-20 minutes.

[0012] Preferably, in the process of obtaining the pretreated ore, the stirring step is as follows: stirring at a stirring speed of 1500 rpm for 15 minutes.

[0013] Preferably, in the process of obtaining pretreated ore, the screening step is to pass it through a 140-270 mesh sieve.

[0014] Preferably, in the process of obtaining pretreated ore, the screening step is to pass it through a 200-mesh sieve.

[0015] Preferably, in the process of obtaining pretreated ore, the centrifugation step is to centrifuge for 1.5-3 minutes under the condition of centrifugation separation factor of 9-11.

[0016] Preferably, in the process of obtaining pretreated ore, the centrifugation step is to centrifuge for 2 minutes under a centrifugation separation factor of 10.

[0017] Preferably, in the magnetic separation step, the magnetic field strength is 1-1.4T.

[0018] Preferably, in the magnetic separation step, the magnetic field strength is 1.2T.

[0019] Preferably, the multiple flotation process includes the following steps: roughing, which involves aeration and foam scraping, collecting the foam as quartz rough, and the remainder as roughing tailings; first cleaning, where the quartz rough is taken, n-dodecyl alcohol, an anionic collector, and a cationic collector are added, the pH is adjusted to 9-11, aeration and foam scraping are performed, and the foam is collected as first flotation quartz ore, with the remainder as first flotation tailings; second cleaning, where the first flotation quartz ore is taken, n-dodecyl alcohol, an anionic collector, and a cationic collector are added, the pH is adjusted to 9-11, aeration and foam scraping are performed, and the foam is collected as second flotation quartz ore, with the remainder as second flotation tailings; Repeat the above steps. In subsequent cycles, the object of the roughing step is the roughing tailings obtained in the previous cycle. Collect the second flotation quartz ore in each cycle, which is the quartz concentrate. The roughing tailings obtained in the last cycle are the feldspar ore. Stop the cycle when the purity increase of the quartz concentrate is no more than 0.2%.

[0020] Preferably, the first flotation tailings obtained in the previous cycle are added to the roughing tailings obtained in the previous cycle before the roughing step in the next cycle, and the second flotation tailings obtained in the previous cycle are added to the first flotation quartz ore before the second cleaning step in the next cycle.

[0021] Preferably, the amounts of n-dodecyl alcohol, anionic collector, and cationic collector are decreased sequentially before the multiple flotation steps, the first refining step, and the second refining step.

[0022] Preferably, the amounts of dodecanol, anionic collector, and cationic collector are halved sequentially before the multiple flotation steps, in the order of the first refining step, and the second refining step.

[0023] Preferably, the inflation time is 0.5-2 minutes and the bubble removal time is 2-4 minutes.

[0024] Preferably, the inflation time is 1 minute and the bubble removal time is 3 minutes.

[0025] Preferably, the anionic collector includes one or more of oleic acid, alkyl sulfonate and alkyl sulfate, and the cationic collector includes one or more of dodecylamine, octadecylamine, dodecyl tertiary amine and octadecyl tertiary amine.

[0026] Preferably, the anionic collector is sodium dodecyl sulfonate, and the cationic collector is dodecylamine.

[0027] Preferably, the amount of n-dodecyl alcohol used is 150-250 g / t.

[0028] Preferably, the amount of n-dodecyl alcohol used is 200 g / t. Preferably, the ratio of the amount of n-dodecyl alcohol to the amount of the cationic collector is 1.875-3.125:1.

[0029] Preferably, the ratio of the cationic collector to the anionic collector is 0.2-1:1.

[0030] Preferably, the ratio of the amount of n-dodecyl alcohol, the cationic collector, and the anionic collector is 1:0.4:2.

[0031] Preferably, the acid used in the high-temperature pickling includes one or more of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid.

[0032] Preferably, the acid used in the high-temperature pickling is a mixture of hydrochloric acid, nitric acid, sulfuric acid and hydrofluoric acid.

[0033] Preferably, the acid used in the high-temperature pickling is a mixture of hydrochloric acid, nitric acid, sulfuric acid, and hydrofluoric acid in a molar ratio of 3:2:1.5:1. In summary, this application includes at least one of the following beneficial technical effects: 1. Deep processing of granite tailings, including screening, magnetic separation, flotation, and acid washing, yields high-purity quartz sand and low-iron feldspar powder, which are then applied to fields such as polycrystalline silicon crucibles for photovoltaics, ultra-white glass, and high-grade ceramic raw materials, thus broadening the application scope and improving the utilization rate of granite tailings. 2. Multiple flotation processes using dodecanol, anionic collectors, and cationic collectors improved the separation of quartz and feldspar, resulting in a quartz concentrate with a purity of 98.5%. Finally, the high-purity quartz sand obtained after acid washing reached a purity of 3N5 grade. 3. By adjusting the pH and adding a dispersant, followed by stirring, sieving, and centrifugation, the dispersion of various components in the granite tailings was improved, and large-particle mineral impurities were removed. Detailed Implementation

[0034] The present application will be further described in detail below with reference to the embodiments. The following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified, specific conditions in the following embodiments were performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the methods used are conventional methods known in the art, and the consumables and reagents used are commercially available. Unless otherwise stated, the technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be applied to the present invention.

[0035] All raw materials used in the examples are commercially available.

[0036] Example 1 Example 1 provides a granite tailings processing technology, including the following steps: Pretreatment: Take granite tailings, adjust the pH of the solution to 10 with NaOH, add sodium hexametaphosphate at a ratio of 1000g / t, scrub for 15min with stirring speed of 1500rpm, and then pass through a 200-mesh standard sieve to remove large mineral impurities to obtain slurry. Centrifuge the slurry for 2min with a centrifugation factor of 10, and take the precipitate obtained by centrifugation to obtain pretreated ore. Magnetic separation: The pretreated ore is subjected to magnetic separation under a magnetic field strength of 1.2T to remove magnetic materials and obtain demagnetized ore; Quartz and feldspar are separated, the magnetic ore is removed, 200 g / t n-dodecyl alcohol is added and reacted for 3 minutes, then 400 g / t sodium dodecyl sulfonate and 80 g / t dodecylamine are added at once and reacted for 3 minutes. Multiple flotation processes are performed, with the following steps: Roughing: Aeration for 1 minute and skimming for 3 minutes, the collected foam is the quartz rough, and the remainder is the roughing tailings; First cleaning: The quartz rough is taken, 100 g / t n-dodecyl alcohol, 200 g / t sodium dodecyl sulfonate and 40 g / t dodecylamine are added, aeration for 1 minute and skimming for 3 minutes, the collected foam is the first flotation quartz ore, and the remainder is the first flotation tailings; Second cleaning: The first flotation quartz ore is taken, 50 g / t n-dodecyl alcohol, 100 g / t sodium dodecyl sulfonate and 20 g / t dodecylamine are added, aeration for 1 minute and skimming for 3 minutes, the collected foam is the second flotation quartz ore, and the remainder is the second flotation tailings; Repeat the above steps. In subsequent cycles, the roughing step is carried out on the roughing tailings obtained in the previous cycle. The first flotation tailings obtained in the previous cycle are added to the roughing tailings obtained in the previous cycle before the roughing step in the next cycle. The second flotation tailings obtained in the previous cycle are added to the first flotation quartz ore before the second cleaning step in the next cycle. The second flotation quartz ore in each cycle is collected to form quartz concentrate. The roughing tailings obtained in the last cycle are feldspar ore. The cycle is stopped when the purity increase of the quartz concentrate is no more than 0.2%.

[0037] Acid washing was performed on the quartz concentrate at 200℃ using a mixed acid solution containing 3.0 mol / L hydrochloric acid, 2 mol / L nitric acid, 1.5 mol / L sulfuric acid, and 1.0 mol / L hydrofluoric acid. The leaching was carried out with electric stirring at a stirring speed of 200 r / min and a liquid-to-solid ratio of 2:1 for 10 h to obtain high-purity quartz sand.

[0038] In this embodiment, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification is half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added is half the amount added during the first purification. Furthermore, the pH is maintained at 10 throughout the quartz and feldspar separation process.

[0039] Example 2 Example 2 provides a granite tailings processing technology. The difference between Example 2 and Example 1 is that in Example 2, the amount of n-dodecyl alcohol used before multiple flotation in the quartz and feldspar separation step is 150 g / t.

[0040] In this embodiment, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification is half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added is half the amount added during the first purification. Furthermore, the pH is maintained at 10 throughout the quartz and feldspar separation process.

[0041] Example 3 Example 3 provides a granite tailings processing technology. The difference between Example 3 and Example 1 is that in Example 3, the amount of n-dodecyl alcohol used before multiple flotation in the quartz and feldspar separation step is 250 g / t.

[0042] In this embodiment, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification is half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added is half the amount added during the first purification. Furthermore, the pH is maintained at 10 throughout the quartz and feldspar separation process.

[0043] Example 4 Example 4 provides a granite tailings processing technology. The difference between Example 4 and Example 1 is that in Example 4, before multiple flotation steps, the amount of sodium dodecyl sulfate added at once is 240 g / t, and the amount of dodecylamine added is 240 g / t.

[0044] In this embodiment, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification is half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added is half the amount added during the first purification. Furthermore, the pH is maintained at 10 throughout the quartz and feldspar separation process.

[0045] Example 5 Example 5 provides a granite tailings processing technology. The difference between Example 5 and Example 1 is that in Example 5, before multiple flotation steps, the amount of sodium dodecyl sulfate added at once is 320 g / t, and the amount of dodecylamine added is 160 g / t.

[0046] In this embodiment, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification is half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added is half the amount added during the first purification. Furthermore, the pH is maintained at 10 throughout the quartz and feldspar separation process.

[0047] Comparative Example 1 Comparative Example 1 provides a granite tailings processing technology. The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the amount of n-dodecyl alcohol used before multiple flotation steps in the quartz and feldspar separation step is 100 g / t.

[0048] In this comparative example, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification was half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added was half the amount added during the first purification. Furthermore, the pH was maintained at 10 throughout the quartz and feldspar separation process.

[0049] Comparative Example 2 Comparative Example 2 provides a granite tailings processing technology. The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the amount of n-dodecyl alcohol used before multiple flotation steps in the quartz and feldspar separation step is 300 g / t.

[0050] In this comparative example, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification was half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added was half the amount added during the first purification. Furthermore, the pH was maintained at 10 throughout the quartz and feldspar separation process.

[0051] Comparative Example 3 Comparative Example 3 provides a granite tailings processing technology. The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the amount of dodecylamine used once before multiple flotation in the quartz and feldspar separation step is 480 g / t, and sodium dodecyl sulfonate is not added.

[0052] In this comparative example, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification was half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added was half the amount added during the first purification. Furthermore, the pH was maintained at 10 throughout the quartz and feldspar separation process.

[0053] Comparative Example 4 Comparative Example 4 provides a granite tailings processing technology. The difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, the amount of sodium dodecyl sulfonate used once before multiple flotation in the quartz and feldspar separation step is 480 g / t, and no dodecylamine is added.

[0054] In this comparative example, during the separation of quartz and feldspar, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added during the first purification was half the amount added before multiple flotations. During the second purification, the amount of n-dodecyl alcohol, sodium dodecyl sulfonate, and dodecylamine added was half the amount added during the first purification. Furthermore, the pH was maintained at 10 throughout the quartz and feldspar separation process.

[0055] Comparative Examples 5-9 Comparative Examples 5-9 provide a granite tailings processing technology. The difference between Comparative Examples 5-9 and Example 1 is that in the quartz and feldspar separation step of Comparative Examples 5-9, n-dodecyl alcohol is replaced with calcium chloride. The amount of calcium chloride used in Comparative Examples 5-9 is shown in Table 1.

[0056] Table 1:

[0057] Testing and Inspection The purity of the quartz concentrate and high-purity quartz sand obtained by the processing techniques of Examples 1-5 and Comparative Examples 1-9 was tested, and the test results are shown in Table 2.

[0058] Table 2:

[0059] The following detailed description of this application is based on the experimental data provided in Table 1-2.

[0060] Referring to the data from Examples 1-5 in Table 2, it can be seen that the purity of the high-purity quartz sand obtained by the processing technology of Examples 1-5 all reached above 99.1%, especially the high-purity quartz sand obtained by the processing technology of Example 1, which reached the highest purity of 99.95%. This indicates that during the adaptation and feldspar separation process, the ratio of the amount of added n-dodecyl alcohol, sodium dodecyl sulfonate and dodecylamine affects the purity of the high-purity quartz sand obtained, and the highest purity of the high-purity quartz sand is obtained when the ratio of the amount of added n-dodecyl alcohol, sodium dodecyl sulfonate and dodecylamine is 1:2:0.4.

[0061] The table shows that the purity of the intermediate product—quartz concentrate—obtained during the processing is higher than that obtained by using the processing techniques in Examples 1-5 (above 90%). This indicates that the processing techniques in Examples 1-5 achieve a higher degree of separation between low-iron feldspar ore and quartz concentrate than those in Comparative Examples 1-9. The high-purity quartz sand produced using the processing techniques in Examples 1-5 can be applied to the field of polycrystalline silicon crucibles for photovoltaic applications, while the low-iron feldspar ore can be used in fields such as ultra-white glass and high-grade ceramic raw materials, thus broadening the application areas and improving the utilization rate of granite tailings.

[0062] Referring to Examples 1 and Comparative Examples 3-9, where sodium dodecylbenzenesulfonate was not used in Comparative Example 3, dodecylamine was not used in Comparative Example 4, and n-dodecyl alcohol was not used in Comparative Examples 5-9, the purity of the high-purity quartz ore obtained by the processing technology of Example 1 was much higher than that obtained by the processing technology of Comparative Examples 3-9. Furthermore, the purity of the quartz concentrate obtained by the processing technology of Example 1 was also higher than that obtained by the processing technology of Comparative Examples 3-9. This indicates that n-dodecyl alcohol, sodium dodecylbenzenesulfonate, and dodecylamine are all indispensable in improving the degree of separation between quartz and feldspar and in improving the purity of high-purity quartz ore.

[0063] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A granite tailings processing technology, characterized in that: The process includes the following steps: taking granite tailings, adjusting the pH, adding a dispersant, stirring, and then sieving to obtain a slurry; collecting the slurry and centrifuging the sediment to obtain pretreated ore; subjecting the pretreated ore to magnetic separation to remove magnetic materials to obtain demagnetized ore; taking the demagnetized ore, adjusting the pH to 9-11, adding n-dodecyl alcohol, anionic collector, and cationic collector, and performing multiple flotation to obtain quartz concentrate and feldspar ore; taking the quartz concentrate, and subjecting it to high-temperature acid washing, stirring, and leaching to obtain high-purity quartz sand. The multiple flotation process includes the following steps: roughing, which involves aeration and foam scraping, collecting the foam as quartz rough, and the remainder as roughing tailings; first cleaning, where the quartz rough is taken, n-dodecyl alcohol, anionic collector, and cationic collector are added, the pH is adjusted to 9-11, aeration and foam scraping are performed, and the foam is collected as first flotation quartz ore, with the remainder as first flotation tailings; second cleaning, where the first flotation quartz ore is taken, n-dodecyl alcohol, anionic collector, and cationic collector are added, the pH is adjusted to 9-11, aeration and foam scraping are performed, and the foam is collected as second flotation quartz ore, with the remainder as second flotation tailings; The above steps are repeated. In subsequent cycles, the roughing step targets the roughing tailings obtained in the previous cycle. The second flotation quartz ore in each cycle is collected to form quartz concentrate. The roughing tailings obtained in the last cycle are feldspar ore. The cycle is stopped when the purity increase of the quartz concentrate is no more than 0.2%. The first flotation tailings obtained in the previous cycle are added to the roughing tailings obtained in the previous cycle before the roughing step in the next cycle. The second flotation tailings obtained in the previous cycle are added to the first flotation quartz ore before the second cleaning step in the next cycle.

2. The granite tailings processing technology according to claim 1, characterized in that: The amounts of dodecanol, anionic collector, and cationic collector are decreased sequentially before the multiple flotation steps, in the order of the first refining step, and the second refining step.

3. The granite tailings processing technology according to claim 1, characterized in that: The inflation time is 0.5-2 minutes, and the bubble removal time is 2-4 minutes.

4. The granite tailings processing technology according to claim 1, characterized in that: The anionic collector includes one or more of oleic acid, alkyl sulfonates, and alkyl sulfates, and the cationic collector includes one or more of dodecylamine, octadecylamine, dodecyl tertiary amine, and octadecyl tertiary amine.

5. The granite tailings processing technology according to claim 4, characterized in that: The anionic collector is sodium dodecyl sulfonate, and the cationic collector is dodecylamine.

6. The granite tailings processing technology according to claim 1, characterized in that: The dosage of n-dodecyl alcohol is 150-250 g / t.

7. The granite tailings processing technology according to claim 1, characterized in that: The ratio of the amount of n-dodecyl alcohol to the amount of the cationic collector is 1.875-3.125:

1.

8. The granite tailings processing technology according to claim 1, characterized in that: The ratio of the amount of the cationic collector to the amount of the anionic collector is 0.2-1:1.

Citation Information

Patent Citations

  • Mineral processing methods for separating potassium feldspar concentrate from potassium-rich slate in Bayan Obo

    CN102284351A

  • Method for recycling single quartz and feldspar from gold flotation tailings

    CN105127003A